Effectiveness of Spiritual Emotional Freedom Technique in Reducing Pain Among Fracture Patients - Putri, Nabila Luqyana; Sepdianto, Tri Cahyo; Mugianti, Sri (Health Access Journal, 2026)
The main complaint in fracture patients is pain, this pain needs to get the right intervention both pharmacologically and non-pharmacologically. The purpose of this research is to determine the effectiveness of SEFT Therapy (Spiritual Emotional Freedom Technique) on reducing pain in fracture patients. This research design is Pre-Experimental with a one group pre-post test approach. The population of fracture patients in the emergency room of dr. Soedono Hospital, East Java Province was 30 respondents. The sample technique is probability sampling with purposive sampling method. Taking instruments to measure the pain level of fracture patients, researchers used the NRS (Numeric Rating Scale) pain tool. The data were processed descriptively followed by the Paired t Test. The results showed that the average pain level before SEFT therapy was 5.13 with a minimum-maximum scale of 2-7 and after SEFT therapy was 4.13 with a minimum-maximum scale of 2-6. The results of statistical tests using the Paired t Test test showed a value of p=0.000 (p<0.05). There is a significant difference in pain levels before and after SEFT therapy. SEFT therapy effectively reduces the pain level of fracture patients and becomes an alternative as non-pharmacological management to reduce the pain level of fracture patients